Legal Regulation of Innovative Developments in the Field of Technical Workings-out as Part of State Socio-Economic Development - LEBEDEV, Aleksandr I.; YANINA, Olga N.; BOKOV, Yuriy A.; BOSENKO, Timur M. (Journal of Advanced Research in Law and Economics, 2019)
The aim of the work is to consider the state regulation of innovation. The analyzed aspects such as the efficiency of government regulation, the scenarios considered state regulation, analyzed the activities of the state in regulation of innovative activity. The economic growth of the country is based on a combination of extensive and intensive factors. Extensive factors are understood as an increase in the mass of resources used in production, intensive factors are an increase in the quality of resources and the efficiency of their use. In the modern era, the possibilities of economic growth through the involvement of new resources are severely limited. Therefore, intensive factors are crucial. Thus, innovation has a decisive influence on macroeconomic indicators. In addition, they affect social stability, the environment, the intensity of international technical cooperation, the level of national security and the competitiveness of the national economy in the world economy. The need for state regulation of innovation processes is primarily caused by their increasing importance for the economy and society as a whole. The state should regulate the innovation process, as it currently determines the prospects for the development of the country. Therefore, the topic of the work is relevant and important. Since innovation is characterized by complexity and high risk. Internal incentives and capacity may not be enough to initiate innovation. External incentives and, in particular, government support can be a decisive driving force.